VD_FINDINFO AP / 2010 / 141 vom 17. Februar 2010 - VD Tribunal cantonal (2010)
MESURE THÉRAPEUTIQUE INSTITUTIONNELLE, ESCROQUERIE, FAUTE | 146 al. 1 CP, 47 CP, 59 al. 1 CP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP, 415 CPP